Classical solutions of linear regulator for degenerate diffusions - Baten, Md Azizul (Hindawi Publishing Corporation, 2006)
We study a stochastic control problem for linear degenerate systems. We establish the existence of a classical solution of the degenerate Bellman equation by the technique of viscosity solutions, and the optimal policy is shown to exist from the optimality conditions.